Matematyka

Autorzy:Aleksandra Ciszkowska, Alina Przychoda, Zygmunt Łaszczyk

Wydawnictwo:WSiP

Rok wydania:2012

Podaj wartość wyrażenia (-3)³ +(-5)², a następnie 4.5 gwiazdek na podstawie 8 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

`(-3)^3+(-5)^2=(-27)+25=(-2)`

a)

`((-3)^3+(-5)^2)^2=(-2)^2=4`

b)

`((-3)^3+(-5)^2)^(-3)=(-2)^(-3)=(-1/2)^3=(-1/8)`

c)

 `((((-3)^3+(-5)^2)^2)/((-3)^3+(-5)^2)^(-3))^(-1)=`   `(((-2)^2)/(-2)^(-3))^(-1)=` `((-2)^(2-(-3)))^(-1)=((-2)^5)^(-1)=(-2)^(-5)`    


d)

 `((((-3)^3+(-5)^2)^2)/((-3)^3+(-5)^2)^(-3))^(-3)*1024=`   `(((-2)^2)/(-2)^(-3))^(-3)*2^10=` `((-2)^(2-(-3)))^(-3)*2^10=((-2)^5)^(-3)*2^10=(-2)^(-15)*2^(10)=2^(-5)`